«Ghent Initiative» and Its Influence on Defense and Security Policy of the EU Countries - K. E. Petrov (Международная аналитика, 2017)
The article considers the appearance and implementation of the concept of pooling and sharing of military resources of the EU countries, also known as “Ghent Initiative”. The conditions are analyzed under which it was suggested as a means of the reduction of military budgets. Individual programs that form parts of it, as well as their impact on the EU policy in the fields of security and defense are reviewed. The prospects of the initiative are also discussed, including the emergence of brand-new spheres within the general outline of defense and security policy, such as, for instance, the issues if cybersecurity. Nowadays due to lasting tensions between national interests and supranational institutional build-up the full-fledged implementation of “Ghent Initiative” in common European version is complicated. However, the search for non-NATO alternative military structures within the EU will be continued.